Nonlinear tracking control of a two link oil palm harvesting manipulator - Shamshiri, Ramin; Wan Ismail, Wan Ishak (International Journal of Agricultural and Biological Engineering, 2012)
Ramin Shamshiri1*, Wan Ishak Wan Ismail2 (1. Department of Agricultural and Biological Engineering, University of Florida, Gainesville, FL 32611, USA; 2. Department of Biological and Agricultural Engineering, Universiti Putra Malaysia, Serdang. Selangor Darul Ehsan, Malaysia) Abstract: Automated harvesting of oil palm trees requires research and development efforts in several robotics areas, including manipulator control. The objective of this paper was to apply nonlinear Lyapunov based control method for joint angles tracking of a two-link oil palm harvesting robot manipulator with uncertain system parameters. Four different controllers, including exact model knowledge, adaptive, sliding mode control and high gain feedback control were proposed and simulated. Stability analyses were performed for each case in the absence and presence of bounded disturbance. The controllers were then compared against each other based on their performances and control efforts. Keywords: harvesting robotics, oil palm, nonlinear control, manipulator control, Lyapunov method DOI: 10.3965/j.ijabe.20120502.002 Citation: Shamshiri R, Wan Ishak W I. Nonlinear tracking control of a two link oil palm harvesting robot manipulator. Int J Agric & Biol Eng, 2012; 5(2): 9